Reproducibility and Robustness Replicability of Gsottbauer et al. (2022) - Ahwaz Akhtar; Hao Ye (Institute for Replication (I4R), 2023)
The relationship between social status and ethical behavior is a widely debated topic in research. In their study, Gsottbauer et al. (2022b) investigate whether higher socio-economic status is linked to lower ethical behavior, using data from two large survey experiments involving over 11,000 participants. In this replication project, we test the computational reproducibility and robustness to the replication of their study, using the provided data and code from the replication package (Gsottbauer et al., 2022a). Nearly all the figures and tables were reproducible-in the process of reproducing the results, some minor rounding or transcription errors were discovered. In testing the robustness replicability, we find consistent results for our extensions. The effort for the replication was manageable, even though the authors treat categorical variables as numeric, or use manually-coded interaction variables (i.e. in regression models). In summary, we applaud the transparency of Gsottbauer et al. (2022b) in facilitating replications, and make some general recommendations for further improvements for data-analysis studies.
Keywords: 330; Replication; Experiment; information provision; inequality; field experiment